Development of an urban canopy model for the evaluation of urban thermal climate with snow cover in severe cold regions. (January 2016) - Shui, Taotao; Liu, Jing; Zhang, Pengcheng; Liu, Shengjun; Zhao, Zhiqing
Abstract: Snow plays an important role in determining heat and moisture exchanges between the underlying surface and atmosphere in winter. However, the effect of snow cover is not considered or assumed to be negligible in existing urban canopy energy balance models. In this paper, a one-dimensional snow model that accounts for heat transfer within snow cover is developed, and the model is implemented into an urban canopy energy balance model to simulate energy and moisture exchanges in cold urban areas with stable snow cover. The numerical methods of the snow model and the urban canopy model are demonstrated first, and the urban canopy model is subsequently used to simulate the thermal climate of a residential area dynamically in Yichun, China during winter. The results indicate that the existence of snow cover decreases the outdoor air temperature by 0.15 °C on average and 1.16 °C at maximum. In addition, the outdoor mean SET* increases 0.43 °C with the removal of snow cover, indicating that the thermal comfort of people outside decreases due to the presence of snow cover. Highlights: Developing a snow model to simulate the energy exchange within the snow cover. Improving an urban canopy energy balance model by coupled with the snow model. Performing field measurements to validate the snow model. Evaluating the effect of the snow cover on the thermal climate and comfort.